MOTIVASI MAHASISWA KAMPUS 1 UNIVERSITAS NEGERI SURABAYA YANG SERING BERKUNJUNG DI COFFEE SHOP - lailautami laila; Sarmini (Kajian Moral dan Kewarganegaraan, 2026)
Coffee shops are no longer just places to enjoy coffee; they have evolved into multifunctional spaces for students, especially those in major cities like Surabaya. Students at Campus 1 of Surabaya State University are no exception. This phenomenon indicates that coffee shops have a greater appeal than simply providing beverages, but also as part of the student life experience. This study aims to identify and understand the motivations of students who frequently visit coffee shops. The theoretical basis used is the concept of "because motive" and "in order to motive" by Alfred Schutz. The research method used is qualitative with a phenomenological approach, with data obtained through in-depth interviews with students who frequently visit coffee shops around campus 1 of Surabaya State University. The results of the study indicate that the motives of students who frequently visit coffee shops are: 1) Waiting for the next class; 2) Continuing to work on unfinished assignments in the campus library; 3) Escaping the negative distractions of boarding rooms when working on assignments; 4) A comfortable coffee shop atmosphere can support student productivity. In order to motive students who frequently visit coffee shops are: 1) Maintaining and improving the semester's cumulative grade point average (GPA); 2) Faster completion of college assignments; 3) Chasing the deadline for submitting college assignments; 4) So as not to repeat courses and graduate on time; 5) Productive dating; 6) Building relationships with fellow students; 7) Looking for inspiration for trendy student style outfits and makeup; 8) Feeding social media accounts.